Mapping and linkage analysis of epistatic QTLs for gynoecious trait (F) in cucumber (Cucumis sativus L.). Issue 3 (4th May 2021) - G., Boopalakrishnan; Jayavel, Sridhar; Behera, Tusar Kanti; Munshi, Anilabha Das; Choudhary, Harshwardhan; Singh, Anupam; Pandey, Manoj Kumar
ABSTRACT: The QTL mapping for gynoecy in cucmber ( Cucumis sativus L.)was carried out by using backcross populations (BC1 F2 & BC1 F3 ) of a cross using two inbred lines; one monoecious with multiple (≥ 5) lateral branching habit cv. Pusa Uday (Indian slicing type) and gynoecious exotic line Gy14 (American pickling type) with few lateral branches (1–2). QTL detection was performed by employing QTL Ici mapping software (version 4.1) of the two mapping populations. We detected seven gynoecious QTLs in two genomic regions (chromosome 5 and 6), on which three significant QTLs ( qGyn 5.1, qGyn 6.5 and qGyn 6.6 ) had higher LOD score (10.5, 26.2, and 24.5) and phenotypic variance (5.9, 14.5 and 14.5%) in BC1 F2 population. However, two significant QTLs ( qGyn 5.1 and qGyn 6.1) accounted for gynoecism which could explain 22.90 and 12.88% of the phenotypic variation with the LOD score of 15.86 and 11.82 in linkage group 5 and 6, respectively in BC1 F3 population. Out of 82 simple sequence repeats (SSR) markers, three (SSR00233, SSR15516 and SSR13251) was found tightly linked and flanked to gynoecious trait QTLs ( qGyn6.5 and qGyn6 .6) in BC1 F2 population at <1.5 cM, which could be used for marker-assisted selection (MAS) in cucumber improvement programmes. In order to increase the productivity of Indian cucumber, the introgressed Indian gynoecious cucumber lines derived from an exotic genetic background using MAS may be directly used as a variety or parent of hybrid.